The Correlation of Vocabulary Mastery and Reading Interest with Quick Reading Ability - Liza Andeska; Akhmad Sutiyono; Tommy Hastomo; Nani Angraini (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2021)
This study describes the relationship between reading interest and vocabulary mastery with the speed reading ability of eighth-grade students of SMPN 3 Sungkai, North Lampung. The researchers use the correlational method to achieve the research objectives. The techniques used in collecting research data are questionnaires, tests, and observations. Research data analysis techniques include requirements analysis tests, statistical analysis, and hypothesis testing techniques. Based on the results of the study, it can be concluded that (1) there is a positive and significant relationship between reading interest and speed reading ability, indicated by a correlation coefficient of 0.766 and a coefficient of determination (R2) of 0.587 or 58.7%, (2) there is a relationship positive and significant correlation between vocabulary mastery and speed reading ability which is indicated by a correlation coefficient of 0.662 and a coefficient of determination (R2) of 0.438 or 43.8%, (3) there is a positive and significant relationship between reading interest and vocabulary mastery with ability speed reading indicated by the correlation coefficient of 0.804 and the coefficient of determination (R2) of 0.646 or 64.6%.